ANALISIS KONTEN MEDIA INSTAGRAM SPEELGOED TOYS TERHADAP CUSTOMER ENGAGEMENT - Irma Sentana; Chandra Hendriyani; Tengku Sitti Rochmah (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
This study aims to analyze the effect of Instagram social media content on customer engagement at Speelgoed Toys, a collectible toy company. Based on the analysis of various types of marketing content, previous social interactions on social media proved to be the main factor that increased customer engagement. The uniqueness of this research lies in the contextual and applicative approach that not only discusses customer engagement theory, but also relates it directly to the social media strategy implemented by local companies. This research uses a descriptive qualitative approach of case study method with a focus on an in-depth understanding of the phenomenon of customer engagement in Speelgoed Toys' Instagram content. This research analyzes how Speelgoed Toys' social media content on customer engagement with the aim of gaining a holistic understanding of audience behavior, perceptions, and motivations. Primary data was obtained through in-depth interviews with business owners, while secondary data was obtained from various sources such as Instagram content documentation and previous marketing reports. The results show that Speelgoed Toys' Instagram content has successfully created a strong customer engagement relationship between the brand and the audience, especially adult collectors who are the main target market. However, even though customer engagement is already quite good, there is still potential for further development by developing the brand's Instagram content.